Nanomaterial and Laser Induced – Breakdown Spectroscopy (LIBS) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
In the present work, the optical emission spectra of Nano- Copper (Cu) plasma have been recorded and analyzed using the laser induced breakdown spectroscopy technique (LIBS). The emission line intensities and plasma parameters were investigated as a function of laser energy. The electron number density (ne) and electron temperature (Te) were determined using the Boltzmann plot method and McWhirter criterion.